Umori preriformistici in un umanista meridionale: Antonio Galateo - Domenico Defilippis (Studia Paradyskie)
In the production of Anthonio De Ferrariis Galateo, academic pontaniano, is possible to individualize a precise position of the author towards the religion and the ecclesiastical apparatuses. In the exposure of the Pater noster, in the Hermit, in the De situ Iapygiae and in the epistolario, the most known humanist in Puglia shows to slant for a religiousness that he am respectful extremely of the dictated evangelical and he openly condemns the behaviors of the tall hierarchies of the Church, since they seem disattendere the message of the Christ. Its positions are revealed a great deal next to those of Erasmo da Rotterdam and they anticipate some of the motivations that would have brought to the Lutheran reform, although Galateo never refuses the supremacy and the orthodoxy of Saint Roman Church. Its thought constitutes an unusual testimony of that modern devotio, that would also have received not little succession in the.